School Closures, Mortality, and Human Capital: Evidence from the Universe of Closures during the 1918 Pandemic in Sweden - Christian M. Dahl; Casper W. Hansen; Peter S. Jensen; Martin Karlsson; Daniel Kühnle (Institute of Labor Economics (IZA), 2023)
This study examines the impact of primary-school closures during the 1918 Pandemic in Sweden on mortality and long-term outcomes of school children. Using the universe of death certificates from 1914-1920 and newly-collected data on school closures across 2,100 districts, we conduct high-frequency event studies at both weekly and daily intervals to show that schools closed in response to local surges in influenza deaths. Faster implementation of school closures significantly reduced peak mortality rates among primary-aged individuals. However, our long-run analysis of approximately 100,000 affected children per grade shows precisely estimated, minor and mostly insignificant effects on longevity, employment, and income.
Keywords: J10; N34; I10; 330; short- and long-run effects; human capital; mortality; 1918 Pandemic; school closures